English for Islamic Studies: A Book Review - Muhammad Nurfazri; Dedi Sulaeman (Gunung Djati Conference Series, 2026)
This review evaluates the book English for Islamic Studies: Reading and Exercise Book by Yuli Astutik and Ruli Astuti. The review begins with a brief introduction to the book, the authors’ background, and the book’s main features. The review then presents a description and evaluation of the book’s content based on its central themes. Through 14 units, the authors explore the integration of English language proficiency and Islamic values, covering social ethics, rituals, health, and the history of Islamic civilization. The authors suggest that English instruction in the context of English for Specific Purposes (ESP) must validate learners’ religious identities. The review concludes that the book is an important tool for English language teaching practitioners in Islamic educational settings. However, there is room for improvement in the range of cognitive tasks.